Application of NRS2002 in Preoperative Nutritional Screening for Patients with Liver Cancer. (27th August 2021) - Huang, Suling; Wang, Shijie; Xie, Yuankang; He, Xiao; Yi, Xiuying; Zhang, Jianhong; Deng, Zuomei; Yin, Ling
Abstract : Objective . To explore the application of NRS2002 in preoperative nutritional screening of patients with liver cancer (LC). Methods . 60 LC patients treated in the First Affiliated Hospital of Gannan Medical University (January 2018–May 2021) were chosen as the research objects, and split into group J without nutritional risk and group Q with nutritional risk according to the results of NRS2002 to compare the preoperative situation, surgery-related indexes, hematological indexes, postoperative recovery, and incidence of complications between the two groups. Results . Group J ( n  = 28) and group Q ( n  = 32) showed no obvious difference in preoperative situation, and patients' liver function indexes were within the normal range. The duration of surgery in group J was notably shorter compared with group Q (P < 0.05 ). Alanine aminotransferase (ALT), aspartate aminotransferase (AST), direct bilirubin (DBIL), and albumin in group J were notably different from those of group Q (P < 0.001 ) at 1 day after surgery. ALT and AST in group J were notably different from those of group Q at 3 days after surgery (P < 0.001 ). No obvious differences were observed in the hematological indexes between the two groups at 5 days after surgery (P > 0.05 ). The total amount of albumin infusion, postoperative hospitalization time, and hospitalization cost in group J were notably lower compared with group Q (P < 0.001 ). The incidence of complications in group J was notably lower compared with group Q (P < 0.05 ). Conclusion . Postoperative recovery of LC patients is closely related to their preoperative nutritional status, and those with poor nutritional status have a high incidence of postoperative complications and long recovery time. NRS2002 can effectively screen the nutritional status of patients and provide reference for prognosis evaluation.